Current research suggests that the future looks brighter for cerebral oxygenation monitoring in preterm infants. (29th January 2015) - Kenosi, M; Naulaers, G; Ryan, CA; Dempsey, EM
Abstract Brain injuries remain a significant problem for preterm infants, despite extensive physiological monitoring. Near infrared spectroscopy (NIRS) monitoring in the neonatal intensive care unit has to date remained limited to research activities. Conclusion This review highlights the increasing clinical application of NIRS in delivery suites and neonatal units. Four randomised controlled trials incorporating NIRS monitoring suggest that the future may indeed be brighter for this technology in the care of very preterm infants.